STUDI LITERATUR REVIEW : ANALISIS PENERAPAN PROTOKOL KESEHATAN DALAM MENEKAN ANGKA KESAKITAN COVID 19 DI PASAR - Muhammad Win Arami; Tati Nuryati (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
Covid 19 became a pandemic disease in 2019, where handling and prevention can be done by observing health protocols. The implementation of the health protocol above will not be optimal if it is not supported by community compliance with the policy. The implementation of COVID-19 prevention and control efforts in the market really requires the leadership role of market managers and the involvement of cross-sectors and officials in controlling the discipline of the market community. The purpose of this literature review is to analyze the application of health protocols in suppressing the COVID-19 morbidity rate in the market. The method used is a literature study. The data used in this study are secondary data derived from national or international scientific articles and case reports in South Jakarta. The databases used are Google Scholar, Pubmed, Science direct Research Gate. Study results from 7 national articles that match the inclusion criteria and topics. This health protocol counseling must be carried out continuously in order to increase public awareness of the dangers of Covid-19 transmission using digital platform media instruments or posters so that the community takes part in disseminating the information